INFLUENCE OF EMOTIONAL INTELLIGENCE, PHYSICAL FITNESS AND COPING STRATEGIES ON FOOTBALL PERFORMANCE POPDA BANTEN STUDENT-ATHLETES 2024 - Nurgofar, Dzulfikar; Setiakarnawijaya, Yasep; Dlis, Firmansyah (Gladi : Jurnal Ilmu Keolahragaan, 2024)
This research aims to determine the direct and indirect influence of emotional intelligence, physical fitness and coping strategies on football performance. The population in this study was 66 athletes from POPDA Banten 2024 using a purposive sampling technique. Data was collected using questionnaires and documentation in the form of match videos. The data was then analyzed using the path analysis method with a quantitative approach. The path coefficient value of emotional intelligence on physical fitness is 0.696;sig= 0.000<0.05 which means that emotional intelligence has a positive effect on physical fitness. The path coefficient value of coping strategies on physical fitness is 0.571;sig= 0.002<0.05, which means that coping strategies have a negative effect on physical fitness. The path coefficient value of physical fitness on football performance is 0.571;sig= 0.048<0.05 which means that physical fitness has a positive effect on football performance. The path coefficient value of emotional intelligence and physical fitness on football performance is 0.510;sig= 0.000<0.05 which means that emotional intelligence has a positive effect on football performance. The coefficient value of coping strategies and physical fitness on football performance is -0.470;sig= 0.000<0.05 which means that coping strategies have a negative effect on football performance.